UNJUK KERJA PERALATAN PENGERING HYBRID (ENERGI MATAHARI DAN GAS) UNTUK PENGERINGAN BIJI COKLAT - Miswar abd; Zulfan Zulfan (Jurnal Mekanova : Mekanikal, Inovasi dan Teknologi, 2021)
This research was conducted to examine the drying system with a hybrid energy source between solar energy and gas fuel for applying cocoa beans. Solar thermal energy is used as the main energy source for this dryer, while the energy source from gas fuel is the main energy back-up when the intensity of the sun's heat drops (afternoon, evening and cloudy weather). The results of this test indicate that the drying performance of the data plate collector with 3 cm thick black sand can eradicate cocoa beans with an initial air content of 65-75% with a duration of 26-28 hours, while the hybrid dryer with heat and gas energy sources can shorten the time. drying to 17-19 hours. Keywords: Hybrid Energy, Gas Fuel, solar intensity, Temperature